PENGARUH KEBIJAKAN VAKSINASI COVID-19 DAN INFORMASI KEBIJAKAN TAPERING OFF TERHADAP IHSG TAHUN 2021-2022 - mustajaabah, risq; Eddy Suprapto; Nugroho Suryo Bintoro; Wildan Syafitri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Currently, there is a Covid-19 pandemic that is spreading throughout the world, including Indonesia. Then the government carried out a Covid-19 Vaccination policy to overcome this problem. Along with the implementation of the Covid-19 Vaccination policy, there was information tapering off information policy. What has an impact on the financial system and the real sector is the depreciation of the exchange rate and the high value of inflation. This resulted in capital outflows which had an impact on the ICI movement. The purpose of this study is to determine the impact of covid-19 vaccination, exchange rates, and inflation on ICI in 2021-2022. Research model used VECM (Vector Error Corection Model) with the help of research tools E-Views. The results obtained from this study show that the Covid-19 Vaccination Policy has an influence on the ICI and based on the IRF analysis of trends due to shock in the peiode has a positive influence. Information on tapering off policy through exchange rate and inflation variables has an influence on the ICI and based on IRF analysis the trend due to shock in that period has a negative influence.